Re-Establishment of an Occlusal Vertical Dimension: A Literature Review - Irfan Dammar; Muhammad Faizal Fachry (Indonesia Prosthodontic Association, 2024)
Background : Determination of the correct Occlusion vertical dimension (OVD) is one of the factors that dentists need to pay attention to in important dental procedures. One of the most important strategies of restorative care is the assessment andre-establishment of the occlusal vertical dimension. Tooth attrition causes changes in facial morphology dimensions and OVD decreases. Discussion: The occlusion vertical dimension (OVD) was the height of the lower third of the face as measured from the point of subnation to gnathion at the maximum intercuspation position. One of the factors that affect a person's occlusion vertical dimension is the presence of tooth abrasion, attrition and tooth loss. One way to improve a patient's occlusion vertical dimension is by rehabilitative action with restorative treatment by making crowns for teeth experiencing anterior attrition. Conclusion: Tooth attrition causes changes in facial morphology dimensions and occlusion vertical dimension decreases. Determination of the correct occlusal vertical dimension is one of the success factors in rehabilitation treatment, because if it is not restored properly, the guard teeth will decrease, damage to the teeth, muscles, TMJ, swallowing and can occur speech disorders.